Календарне технічне обслуговування простої системи з урахуванням мінімального аварійного поновлення - Peschansky, A. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
Strategy for minimal fallback renewal with periodical total replacement is considered taking into account the time of renewal. For single-component systems, an alternating process of minimal renewal is introduced and its asymptotic behavior is investigated using tauberian theorems. Optimal terms of total replacement are determined.